Pertumbuhan Ulat Sutera Bombyx mori (Lepidoptera: Bombycidae) pada Berbagai Sumber Protein dalam Pakannya - . Santoso; Damiana Rita Ekastuti (Jurnal Ilmu Pertanian Indonesia, 2013)
Silkworm rearing has high economical value for producing silk material and other beneficial biological materials such as enzyme, antibacterial agent, and antioxidant. For those purposes, it is important to continuously support high quality feed in the silkworm rearing.This study was aimed to evaluate study the growth of silkworm Bombyx mori fed with artificial diet containing different resources of protein (blood meal or soybean meal). The experiment used completely randomized design 5 five treatments artificial feed formulas and 20 repetitions. Each experiment unit consisted of 1 larvae that was reared individually and given different feed. Formula A: 100% blood meal (BM); B: 75%  (BM) + 25% soybean meal (SM); C: 50% (BM) + 50% (SM); D: 25% (BM)+ 75% (SM); and E: 100% SM. Parameters measured were the feed consumption/larvae, opproximate digestibility, ECI (efficiency of conversion of feed ingested), ECD (efficiency conversion of feed digestibility), and body weight gain in fourth and fifth of the larvae instar. Oxygen consumption were measured on the fifth day of the fifth instar before meal and one hour after meal. The result showed that resource of protein did not significantly affect the parameters on the fourth instar, but significantly affected on the fifth instar larvae. Increment of soybean meal in artificial diet increasing oxygen consumption, and resulted decreassing of ECI and ECD value on the fifth instar larvae.